2014
DOI: 10.1128/jvi.02782-13
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of Flavivirus NS4B Protein

Abstract: Flavivirus replication is mediated by a complex machinery that consists of viral enzymes, nonenzymatic viral proteins, and host factors. Many of the nonenzymatic viral proteins, such as NS4B, are associated with the endoplasmic reticulum membrane. How these membrane proteins function in viral replication is poorly understood. Here we report a robust method to express and purify dengue virus (DENV) and West Nile virus NS4B proteins. The NS4B proteins were expressed in Escherichia coli, reconstituted in dodecyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 37 publications
5
88
0
Order By: Relevance
“…For NS4B protein, two bands, representing a monomer (28 kDa) and dimer (56 kDa), were observed. The result is consistent with our previous result that NS4B could dimerize (36). Western blotting showed that antibodies against DENV-2 NS4A or NS4B could specifically detect various oligomeric forms of recombinant proteins (Fig.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…For NS4B protein, two bands, representing a monomer (28 kDa) and dimer (56 kDa), were observed. The result is consistent with our previous result that NS4B could dimerize (36). Western blotting showed that antibodies against DENV-2 NS4A or NS4B could specifically detect various oligomeric forms of recombinant proteins (Fig.…”
Section: Resultssupporting
confidence: 82%
“…In addition to the DENV-2 NS4A-NS4B interaction, recent studies showed that DENV-2 NS4A or NS4B alone could oligomerize (20,36). The latter findings were confirmed by the current result that recombinant NS4A of DENV-2 formed high-order oligomers and that recombinant NS4B formed dimers on SDS-PAGE gels (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations